Simultaneous quantification of human glandular kallikrein 2 and prostate-specific antigen mRNAs in peripheral blood from prostate cancer patients. - Ylikoski, A; Karp, M; Pettersson, K; Lilja, H; Lövgren, T (2001)
We present a multiplexed and internally calibrated quantitative reverse transcription-PCR (QRT-PCR) assay to detect human glandular kallikrein 2 (hK2) and prostate-specific antigen (PSA) transcripts in blood samples from healthy subjects and prostate cancer (PC) patients. The assay detected 50 copies of hK2 and PSA mRNA, and 1 PSA- and 10 hK2-expressing LNCaP cells in the presence of 2.5 x 10(6) PSA- and hK2-negative cells. In PC patients, 20 of 25 and 19 of 25 gave detectable PSA and hK2 mRNAs, respectively. Number of hK2 mRNA copies was significantly higher than that of PSA mRNA copies in patients with biochemically progressive (P = 0.02) PC, and with locally advanced and metastasized (P = 0.004) PC. Patients with rapidly progressive and hormone refractory PC gave detectable hK2 mRNA only in 2 of 8 and PSA mRNA in 3 of 8 patients. Neither PSA nor hK2 mRNAs were detected in 16 healthy subjects. PSA and hK2 discriminated PC patients with biochemically progressive and advanced disease from the controls and from the aggressive distant metastatic disease. The assay provides a reliable quantification of the number of hK2 and PSA mRNA copies, allows to discriminate PC cases from healthy subjects, and offers a tool for further studies on molecular staging of PC.